Optimization of Institutional Roles Based on Regional Leadership Commitment (A Case Study in Garut Regency) - Widaningsih; Rulandari, Novianita; Ulumudin, Aceng (Yayasan Ilomata, 2024)
The policy of decentralization and regional autonomy in Indonesia aims to promote regional development by granting authority to regions to administer governance and development. However, the implementation of this policy still faces various challenges, including limited community involvement, low cooperation among regional governments, as well as constraints in regional capacity and finances. This research aims to optimize the role of regional institutions in regional development, focusing on five districts in Garut Regency. The research method used is qualitative with descriptive analysis, aiming to comprehensively describe the role of regional institutions in regional development. The findings of this research conclude that regional governance in Indonesia has undergone significant changes after implementing decentralization. Sub-districts, previously considered ordinary regional entities, have now become more significant entities within the framework of regional governance. This change reflects efforts to provide greater autonomy to regions in managing local governance and development affairs. Thus, sub-districts play a more proactive role in formulating policies, managing resources, and advancing development at the local level. However, these changes also bring implications such as potential conflicts among institutions and challenges in optimizing the effectiveness of regional governance as a whole. The optimal effectiveness of institutions will function well when there is strong commitment from regional leaders to ensure that these changes align with the goals of regional development and the interests of the communities they serve.